EFFICIENCY OF MICROPULSE LASER (532 NM, 577 NM, 810 NM) THERAPY IN ACUTE CENTRAL SEROUS CHORIORETINOPATHY - Savich, V. V.; Zabarouski, I. H.; Malinouskaya, I. I.; Sidorovich, A. R.; Kharoshykh, K. P. (Zhurnal Grodnenskogo gosudarstvennogo medit͡s︡inskogo universiteta, 2025)
Background. This article discusses the clinical results of using laser technologies in the treatment of one of the vascular diseases of the fundus - central serous chorioretinopathy. Objective. To compare the results of treating acute central serous chorioretinopathy with micropulse laser therapy with green (532 nm), yellow (577 nm) and infrared (810 nm) radiation spectra. Material and methods. The study included 59 people (59 eyes) diagnosed with acute central serous chorioretinopathy. Patients were comprehensively examined using standard general ophthalmological methods before surgery and 1 and 3 months after. All patients were divided into three groups. In group 1, micropulse laser therapy was performed with green (532 nm), in group 2 - with infrared (810 nm) and in group 3 - with yellow (577 nm) laser radiation spectra. Results. After 1 month, complete adhesion of the neuroepithelium in the central zone of the retina occurred in all cases, an increase in visual acuity and photosensitivity was revealed. After 3 months, positive dynamics of an increase in visual acuity and central photosensitivity were noted, and there wasn’t any case of neuroepithelium detachment. Conclusions. The results of the study showed the effectiveness of micropulse laser therapy in the acute form of central serous chorioretinopathy and allow us to conclude that the use of laser radiation of the yellow spectrum (577 nm) is preferable.